Rancang Bangun Sistem Informasi Tracer Study Berbasis Website di SMK PGRI 35 Solokan Jeruk - Setiawan, Rizal; Rohmanto, Ricky; Rachman, Tonton Taufik (Jurnal Dimamu, 2024)
SMK PGRI 35 Solokan Jeruk Kabupaten Bandung is an educational institution under the auspices of the Trustees of the Association of Indonesian Teachers' Educational Institutions (YPLP PGRI) with the guidance of YPLP PGRI West Java Province. The design of the Tracer Study information system is a system created to trace alumni (Tracer Study) at SMK PGRI 35 because there is no information that can support adding accreditation value, how long the waiting period for graduates to get a job, how relevant the curriculum of the field of study is to type of work, position placement, location, and work situation. Therefore, a website-based Tracer Study information system is needed, namely using the system development method approach used is Object Oriented Analysis and Design (OOAD) while the model used is Rational Unified Process (RUP) with a development tool, namely Unified Modeling Language (UML). The results showed that this program makes it easier for schools to manage alumni data and makes it easier for schools to track alumni data so that it can support the addition of accreditation scores, how long the waiting period for graduates to get a job, how relevant the field of study is to the type of work, position placement, location, and job situation.